Co-milling as a synergy factor for co-firing. A case study of wood/coal blends - A.G. Matveeva; Yu.F. Patrakov; A.I. Sechin; P.E. Plyusnin; A.V. Kuznetsov; E.M. Podgorbunskikh; V.A. Bukhtoyarov; A.L. Bychkov; I.O. Lomovsky; O.I. Lomovsky (Carbon Resources Conversion, 2023)
It is known that simple adding of wood allows one to accelerate the ignition of powder mixtures compared to the situation when pure coal is used. This study focuses on testing the hypothesis about the effect of co-milling coal and wood on their co-firing: is the case of composite powdered fuels should ensure the maximum possible efficiency of heat and mass transfer? Firstly, we will show that co-milling of coal and wood leads not independent size reduction of two materials but gives composite powder – coal-covered wood. For the composite fuel further reduction of the ignition delay time of air suspension and reduction of the limit volume concentration required for flame propagation have demonstrated. Obtained synergy also manifests in thermogravimetry. Here we propose a simple method for analyzing the mass loss curves. For any coal-to-wood sawdust ratio, combustion of the composites and mixtures both can be viewed as a weighted sum of the curves of individual components. But only in the case of composites calculated sawdust content is higher than the actual one: the mass loss is redistributed towards the stage occurring at lower temperatures due to geometry of wood/coal contact.